Honokiol acts as an AMPK complex agonist therapeutic in non-alcoholic fatty liver disease and metabolic syndrome - Ruifeng Tian; Jinjie Yang; Xiaoming Wang; Shuaiyang Liu; Ruixiang Dong; Zhenya Wang; Zifeng Yang; Yingping Zhang; Zhiwei Cai; Hailong Yang; Yufeng Hu; Zhi-Gang She; et al. (BMC, 2023)
Abstract Background Non-alcoholic fatty liver (NAFLD) and its related metabolic syndrome have become major threats to human health, but there is still a need for effective and safe drugs to treat these conditions. Here we aimed to identify potential drug candidates for NAFLD and the underlying molecular mechanisms. Methods A drug repositioning strategy was used to screen an FDA-approved drug library with approximately 3000 compounds in an in vitro hepatocyte model of lipid accumulation, with honokiol identified as an effective anti-NAFLD candidate. We systematically examined the therapeutic effect of honokiol in NAFLD and metabolic syndrome in multiple in vitro and in vivo models. Transcriptomic examination and biotin-streptavidin binding assays were used to explore the underlying molecular mechanisms, confirmed by rescue experiments. Results Honokiol significantly inhibited metabolic syndrome and NAFLD progression as evidenced by improved hepatic steatosis, liver fibrosis, adipose inflammation, and insulin resistance. Mechanistically, the beneficial effects of honokiol were largely through AMPK activation. Rather than acting on the classical upstream regulators of AMPK, honokiol directly bound to the AMPKγ1 subunit to robustly activate AMPK signaling. Mutation of honokiol-binding sites of AMPKγ1 largely abolished the protective capacity of honokiol against NAFLD. Conclusion These findings clearly demonstrate the beneficial effects of honokiol in multiple models and reveal a previously unappreciated signaling mechanism of honokiol in NAFLD and metabolic syndrome. This study also provides new insights into metabolic disease treatment by targeting AMPKγ1 subunit-mediated signaling activation.